ANALISIS PROSES PENATALAKSANAAN HIPERTENSI (STUDI KASUS DI PUSKESMAS PURWOYOSO KOTA SEMARANG) - Irana Eka Wardana; Ayun Sriatmi; Wulan Kusumastuti (Jurnal Kesehatan Masyarakat (Undip), 2020)
The number of hypertensive patients in Purwoyoso Public Health Center has increased from 2016 to 2018. However, the coverage of hypertensive patients who seek treatment regularly is still low and far from the 100% target coverage. The purpose of this study is to describe the management of hypertension in PIS-PK in Purwoyoso Public Health Center, Semarang City. This research is a qualitative research with a descriptive analytic approach. Data collection using in-depth interviews were selected based on purposive sampling techniques. The research subjects were PTM Program Holders, Doctors, Nurses, PIS-PK Coordinators, Head of Puskesmas and four patients with hypertension. The aspects studied were the diagnosis of hypertension, lifestyle interventions, pharmacological efforts and medication adherence, and the referral system. The results showed that the patient only did a one-time examination so that it affected the process of providing education, administering medication and taking medication compliance, as well as the patient's unwillingness to be referred. There are several obstacles in the management of hypertension, including patient busyness, distance to the puskesmas, the level of patient awareness in conducting routine checks, low participation in educational activities, not taking drugs again after the drugs run out, and do not want to be referred. The availability of Posbindu to conduct early detection of hypertension only takes place in three hamlet in Kalipancur. In this study, suggest officers provide drug counseling to improve medication adherence and maximize the role of families in supervision of hypertension sufferers.